Medical insurance integration improves migrant workers’ employment quality: Evidence from China’s URRMI reform - Gao, Yixin; Yu, Wenguang; Yu, Xinran; Huang, Yujuan (Frontiers in Public Health, 2025)
This study employs a staggered difference-in-differences approach combined with propensity score matching to evaluate the impact of the Urban-Rural Resident Medical Insurance (URRMI) integration on the employment quality of rural–urban migrant workers. Drawing on data from the 2014–2020 waves of the China Family Panel Studies (CFPS), the analysis constructs a multidimensional employment quality index encompassing wage income, social protection, job stability, and working hours. Mediation analysis identifies two key transmission channels: reduced out-of-pocket medical expenses and improved health status. The empirical results show that URRMI significantly enhances employment quality, with particularly notable improvements in wages, social protection coverage, and employment stability. Heterogeneity analysis further indicates that the policy effects are more pronounced among older workers, in eastern provinces, and within the primary and secondary sectors. These findings contribute new empirical evidence on the labor market implications of social insurance reform and provide timely policy insights to support the transformation of rural migrant workers into “new urban citizens” in the context of China’s inclusive urbanization agenda.